Investigation of the Structural and Dynamical Properties of Cu+ in Liquid Ammonia: A Quantum Mechanical Charge Field (QMCF) Molecular Dynamics Study - Wahyu Dita Saputri; Karna Wijaya; Ria Armunanto (Universitas Gadjah Mada, 2017)
A quantum mechanical charge field (QMCF) molecular dynamics (MD) simulation has been carried out to describe the structural and dynamical properties of Cu+ ion in liquid ammonia. The first and second shells were treated by ab initio quantum mechanics at the Hartree−Fock (HF) level with the DZP-Dunning basis set for ammonia and LANL2DZ ECP basis set for Cu. The system was equilibrated for 4 ps, then the trajectory data was collected every fifth step for 20 ps at 235.15 K. The structural analysis showed that in the first solvation shell, Cu+ is solvated by 4 ammonia molecules forming a stable structure of tetrahedral with Cu-N bond length of 2.15 Å, whereas in the second solvation shell there are 29 ammonia molecules that have an average distance of 4.79 Å to Cu+ ion. Mean residence time of 3.06 ps was observed for the ammonia ligand in the second solvation shell indicating for a highly unstable structure of the solvation shell. The obtained structure of the first solvation shell from this simulation is in excellent agreement with experimental data.